BUDAYA KOMUNIKASI MILITER (Studi Etnografi di Kogartap I/Jakarta) - Hakim, Brigifia Gadista; Fajarina, Fajarina (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the military communication culture of ethnographic studies in Kogartap I/Jakarta. This study uses qualitative research methods by conducting interview techniques to collect data. This research was conducted using an ethnographic research design. Ethnography is the work of describing a culture. Generally, ethnography is used by some researchers to understand other cultures. The main goal is to understand a view of life from the perspective of indigenous people. Data and information were analyzed descriptively using data reduction techniques, data presentation and drawing conclusions. From the results of this research, Searle's speech act theory approach and organizational culture theory provide an analytical framework for evaluating military communication culture in Kogartap I/Jakarta. The interactions resulting from this theory create a military communication culture in Kogartap I/Jakarta in accordance with the speech act theory by Searle and Bureaucracy and a creative culture that the commander has a strong desire to control his environment, including members.